Teeth as lithic raw material: Experiments and use-wear analysis - Parmigiani, Vanesa Esther (2023)
This paper explores the archaeological and ethnographic evidence on use of rodent teeth as instruments, without direct modification (without manufacturing), in replacement of lithic raw materials. There are ethnographic records that describe the use of teeth, extracted from the jaw by direct manual grip or use of handles, and also used inside the jaw, which functions as a handle. Most of the teeth that appear in archaeological contexts have been studied within the framework of zooarchaeological analysis, however, there is the possibility that the dental pieces have been used as instruments, although this has rarely been considered.The objective of this work is present the results of a comparative study of experimental work, which we carried out with beaver (Castor canadensis) and capybara (Hydrochoerus hydrochaeris), and to discuss their similarities and differences with the traces of use of lithic material. Through macro- and microscopic analysis (Stereomicroscope and metallographic microscope), we were able to characterize and explain the natural use signs of the teeth and differentiate them from the anthropic use signs produced when they are used as instruments. These traces on a macro- and microscopic scale, have different characteristics depending on the material worked and the kinematics used, and at the same time show similarities with the traces that occur on certain lithic materials. Consequently, we believe that it is possible to develop functional analyzes on teeth of different animal species, and that these analyzes will contribute to our knowledge about the life forms of past societies.